Overexpression of Golgi Protein CYP21-4s Improves Crop Productivity in Potato and Rice by Increasing the Abundance of Mannosidic Glycoproteins - Park, Hyun Ji; Lee, Areum; Lee, Sang Sook; An, Dong-Ju; Moon, Ki-Beom; Ahn, Jun Cheul; Kim, Hyun-Soon; Cho, Hye Sun (Frontiers in Plant Science, 2017)
CYP21-4 is a novel Golgi-localized cyclophilin protein involved in oxidative stress tolerance. Here, we generated transgenic plants overexpressing AtCYP21-4 and OsCYP21-4 in potato and rice, respectively. The stems and roots of AtCYP21-4overexpressing potato plants were longer than those of wild-type (WT) plants, which resulted in heavier tubers. In vitro tuberization in the transgenic potato also resulted in significantly greater tuber number and weight, as well as a shorter time to microtuber formation. Similarly, OsCYP21-4overexpressing transgenic rice plants had higher biomass and productivity with longer early-stage internodes than the WT and higher seed weight. Immunoblot analysis with CYP21-4 antibody showed that these productivity-enhancing phenotypes were associated with high CYP21-4s protein expression. Anatomically, transgenic potato stems exhibited higher lignin content in xylem cells and thicker leaves. In addition, relative content of mannosidic glycoproteins per unit of total protein was above 20% in transgenic potato tubers and rice grains. Based on these findings, we propose that CYP21-4s are involved in the growth and development of plant vegetative and storage tissues via their effects on glycoprotein abundance or glycan processing in the Golgi apparatus. Thus, increasing CYP21-4s expression in crops could represent an alternative way to increase crop productivity and yield.